ENHANCING STUDENTS SPEAKING SKILL THROUGH ACTING PLAY SCRIPTS (APS) TECHNIQUE - Herlina Herlina; Marleni Marleni; Mega Prasrihamni (Esteem Journal of English Education Study Programme, 2024)
During the process of learning to speak, students often encounter various challenges. Many students exhibit passivity in speaking lessons and lack confidence when speaking in front of the class due to limited vocabulary and a lack of conceptual understanding. The researcher aimed to determine whether the use of "Acting Play Scripts" (APS) in teaching speaking could improve students' speaking skills. The research problem focused on the effectiveness of teaching speaking through the APS technique for students in the English Department of PGRI University Palembang. The objective was to assess the effectiveness of the APS technique in enhancing students' speaking abilities. The study specifically concentrated on students' speaking proficiency in English and utilized a pre-experimental method with a one-group pre-test and post-test design. The researcher selected a single class, namely the 5A class of fifth-semester students from the English Department, comprising 33 students. The findings revealed that the average score in the pre-test was 63.80, while the average score in the post-test was 71.51. The significance level was set at 5%, with a degree of freedom (df) of 32. The critical value of the t-table was 1.6938, and the t-obtained was 55.07. Therefore, the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted, indicating that teaching speaking through the APS technique was effective for students in the English Department of PGRI University Palembang. The APS technique resulted in improvements in students' speaking abilities, including their mean scores, their ability to express ideas using appropriate vocabulary and grammar, and their pronunciation development. The implementation of the APS technique in the speaking classroom exhibited strengths, such as increased student participation and enhanced speaking skills.